Topical ciprofloxacin induced ocular toxicity: case report - Deb, Uttiya; Ray, Soumya; Biswas, Supreeti (International Journal of Basic & Clinical Pharmacology, 2019)
Ciprofloxacin is a commonly used fluoroquinolone group of antimicrobial which is used for treating infective conditions like community acquired pneumonia and urinary tract infections. A patient of cataract was treated with ciprofloxacin eye drop as her pre-operative medication. She presented after four days with itching and redness in her right eye with swelling of the peri-orbital skin. We report this rare case where topical application of ciprofloxacin was responsible for the ocular symptoms.